EARLY GROWTH AND STAND VOLUME PRODUCTIVITY OF SELECTED CLONES OF Eucalyptus pellita - Setyaji, Teguh; Sunarti, Sri; Nirsatmanto, Arif (Indonesian Journal of Forestry Research, 2016)
Tree improvement program for Eucalyptus pellita in Center for Forest Biotechnology and Tree Improvement (CFBTI) was started in 1994. The programs are now beginning their third-generation of breeding which have relied on recurrent selection through establishing open-pollinated seedling seed orchard. Using current technologies, several Industrial Forest Companies in Indonesia are pursuing clonal forestry program with E. pellita to increase plantation productivity using selected clones from comprehensively field testing. This study was aimed to evaluate the early growth and stand volume productivity of selected clones of E. pellita as a part of a breeding program for pulpwood conducted by CFBTI.Â  Two clonal trials of E. pellita were established in Central Java with two different plot configurations: single tree-plot and multiple tree-plot. Measurement at the trials was done at two years age involving tree height, diameter, stem volume and stand volume. The results of study showed that among the clones were significantly different for all traits accessed. All of tested clones exceeded the control seedling of F-1 generation by 9-50% for height, 10-36% for diameter and 22-137%Â  for stem volume. Clone repeatability ranged from 0.7-0.9, with corresponding individual ramet repeatability ranged from 0.2-0.4. The outperformed of the best three selected clones in single tree-plot trial was consistent when planted in multiple tree-plot trial with stand volume productivity at given age reached 15 m3/ha.